Standard triple therapy in Helicobacter pylori eradication in Turkey: Systematic evaluation and meta-analysis of 10-year studies - Sezgin, Orhan; Aydın, Mehmet Kasım; Özdemir, Asena Ayça; Kanık, Arzu Emine (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: This study aims at evaluating the mean eradication rate by a systematic compilation of the studies which involved the standard triple therapy (STT) in first-line Helicobacter pylori (Hp) eradication in Turkey over a period of 10 years between 2004 and 2013 using the meta-analysis method. Materials and Methods: The systematic compilation and meta-analysis were carried out according to the PRISMA standards defined in the Cochrane handbook. The results of full-text studies published in national and international journals in English and Turkish languages on Turkish population in a period of 10 years, from 2004 to 2013, are included in this study. The studies include open-label trials, controlled trials, treatment arms, and case series that included a triple therapy regimen consisting of standard doses of a proton pump inhibitor (PPI; omeprazole 20 mg BID, lansoprazole 30 mg BID, pantoprazole 40 mg BID, esomeprazole 40 mg BID, or rabeprazole 20 mg BID) along with clarithromycin 500 mg BID and amoxicillin 1 g BID for 7-14 days. They were scanned electronically via the search engines Google Scholar, PubMed, and the Turkish Medicine Index using specific keywords. The related keywords used were Turkey, Helicobacter pylori, infection, standard triple treatment, first-line therapy, eradication, omeprazole, lansoprazole, pantoprazole, rabeprazole, esomeprazole, clarithromycin, and amoxicillin. Studies carried out with adults were included in the evaluation. The publication year of the studies and the included number of patients, their age, gender, treatment duration (7, 10, and 14 days), and PPIs used were evaluated by two separate gastroenterologists and biostatisticians. Studies that used at least one reliable method (histology, urea breath test (UBT), or Helicobacter pylori stool antigen (HpSA) test) four weeks after completing the treatment for the control of Hp eradication were included. Only naive patients were accepted, and patients who had previously received eradication treatment were excluded. The effectiveness of the Hp eradication was analyzed using an intention-to-treat (ITT) or per-protocol (PP) analysis. Results: The STT regime of 45 studies complying with the inclusion criteria was evaluated. A total of 3715 patients were included in the study. Of the 3010 patients whose gender information was available, 55% were women and 45% were men; the weighted age average given explicitly in the studies was 42.14±0.67. The treatment lasted for 14 days in 42 studies, for 7 days in six studies, and for 10 days in 1 study. The eradication rates evaluated according to the ITT and PP analyses were 60% (95% CI: 56%-63%) and 57% (95% CI: 51%-62%), respectively. The rates for 7 days of treatment were 57% (95% CI: 46%-68%) and 60% (95% CI: 51%-67%) and for 14 days of treatment were 60% (95% CI: 56%-63%) and 56% (95% CI: 50%-62%), respectively. The ITT eradication rate of the only 10-day study was 78% (95% CI: 66%-86%). In the meta-regression analysis, the treatment duration, PPI, age, and gender ratio (women/men) used for the ITT analysis had no effect. The gender ratio and age were not considered in this analysis because they were not clearly stated in studies using the PP analysis. The duration of treatment and the PPI used had no effect. Conclusion: A systematic meta-analysis of studies conducted during the period 2004-2013 in Turkey revealed that the rate of first-line Hp eradication using STT was unacceptably low, and the duration of treatment and PPI used made no difference. Cite this article as: Sezgin O, Aydın MK, Özdemir AA, Kanık AE. Standard triple therapy in Helicobacter pylori eradication in Turkey: Systematic evaluation and meta-analysis of 10-year studies. Turk J Gastroenterol 2019; 30(5): 420-35.